Development of a Project-Based Design Learning Model to Increase Student Creativity - Ika Yuniwati; Haziq Idris; Sri Dewi Lisnawaty; Pahmi Pahmi (Journal of Loomingulisus ja Innovatsioon, 2025)
The development of creativity is crucial in design education, as it fosters innovative thinking and problem-solving skills essential for success in creative industries. This study addresses this gap by developing a project-based design learning model to enhance student creativity. By incorporating real-world design projects into the curriculum, students are encouraged to apply their knowledge in practical settings, fostering critical thinking and creative exploration. The primary aim of this research is to develop and evaluate a project-based learning model that increases student creativity in design education. The research follows a design-based methodology, implementing the model in a classroom setting and assessing its impact on student creativity. Data were collected through pre- and post-assessments of creativity, student surveys, and interviews with both students and instructors. The findings show that the project-based learning model significantly improved students' creativity. Students exhibited enhanced problem-solving abilities, innovative thinking, and a stronger capacity for collaboration. Moreover, the hands-on approach encouraged deeper engagement with design concepts and promoted an increased sense of ownership over their learning process. In conclusion, the project-based design learning model proved to be an effective strategy for fostering creativity in design students.